Oral History and Memory in Geografy Science: : The Case of Haitians Immigrants in Cascavel, PR, Brazil (Terr@ Plural, 2022)
This study highlights the importance of using oral history and memory in geographic research. These methodologies provide the opportunity to fully report the experiences lived by the interviewees. Essentially qualitative, with theoretical foundations of Cultural Geography, Human Geography, and phenomenological interpretation methods, the research is based on the collection of testimonials from Haitian immigrants living in Cascavel (PR) who came in greater numbers to Brazil after the earthquake that struck the country in 2010. The intention was to use the experiences of these people as an example of the current Haitian mobility to Brazil.
Keywords: Oral sources; Fenomeology; Hatian immigrants